Structural, Topological, and Superconducting Properties of Two‐Dimensional Tellurium Allotropes from Ab Initio Predictions. Issue 2 (14th January 2021) - Zhao, Chunxiang; Cai, Xiaolin; Liu, Liangliang; Liu, Chengyan; Zeng, Zaiping; Niu, Chunyao; Xia, Congxin; Jia, Yu
Abstract: The discovery of tellurene has effectively extended the realm of two‐dimensional (2D) elemental materials to group‐VI, which demonstrates promising potential in next‐generation electronic and optoelectronic device applications. Beyond the three prevailing structural phases of tellurene, it is further predicted 31 2D tellurium allotropes combining the particle‐swarm optimization (PSO) searches with density functional theory (DFT) calculations. The corresponding dynamic and thermal stability are examined by both phonon spectrum calculations and ab initio molecular dynamics (AIMD) simulations. Those 2D tellurium allotropes can be well categorized in terms of their intrinsic number of atomic layers, and cohesive energy. It is found that the allotropes with tri‐atomic layers are energetically most favorable, and mainly demonstrate semiconducting feature at larger cohesive energies. Four of the bi‐atomic‐layer allotropes with larger cohesive energies exhibit topological insulating feature, and two with slightly smaller cohesive energies are intrinsic superconductors with critical temperature Tc (≈8 K) competing with their bulk counterpart at high pressure. Interestingly, both topological and superconducting properties can co‐exist in one of those bi‐atomic‐layer allotropes, which is unique in the elemental 2D materials ever reported. The present study enriches the 2D tellurium allotropes and provides a viable platform for exploring novel functionalities for future device applications. Abstract : Thirty‐one two‐dimensional (2D) tellurium allotropes with different number of atomic layers are predicted through combining the particle‐swarm optimization (PSO) searches with density functional theory (DFT) calculations. Their structural stabilities and various electronic properties (including metallic, semiconducting, topological, superconducting, and topological superconducting properties) are identified by state‐of‐the‐art calculations. The present results enrich the structure and properties of the 2D tellurium allotropes.